Therapeutic Opportunities for Food Supplements in Neurodegenerative Disease and Depression - Businaro, Rita; Vauzour, David; Sarris, Jerome; Münch, Gerald; Gyengesi, Erika; Brogelli, Laura; Zuzarte, Pedro (Frontiers in Nutrition, 2021)
Emerging evidence is showing nutrition as a crucial factor in the high prevalence and incidence of neurodegenerative mental disorders. Preventive interventions on neuroinflammation seem to be able to interfere with neurodegeneration. Supplementation of essential nutrients, such as long-chain-polyunsaturated fatty acids, vitamin E and mineral elements, may minimize inflammation, enhancing antioxidative defense, and lowering the risk and incidence of age-related diseases, such as cardiovascular diseases and neurodegenerative diseases. This manuscript reviews the current evidence on the role of neuroinflammation in the pathophysiology of neurodegenerative and mental disorders, and preventive strategies for food supplementation in these neuropsychiatric diseases. Dietary supplementation-based strategies have been demonstrated to be effective in subjects with mild cognitive impairment, while weaker results have been obtained in patients with advance neurodegenerative disease. Adjunctive supplementation has also been demonstrated to improve depression, this being of marked benefit considering the comorbidity between cognitive impairment/dementia and depression. Further research is needed to improve the prescriptive precision of supplementation in patients, and to better understand potential interactions with clinical and pharmacokinetic factors.